Objective evaluation of chemotherapy-induced peripheral neuropathy using quantitative pain measurement system (Pain Vision®), a pilot study - Junya Sato; Megumi Mori; Satoru Nihei; Satoshi Takeuchi; Masahiro Kashiwaba; Kenzo Kudo (BMC, 2017)
Abstract Background In an evaluation of chemotherapy-induced peripheral neuropathy (CIPN), objectivity may be poor because the evaluation is determined by the patient's subjective assessment. In such cases, management of neuropathy may be delayed and CIPN symptoms may become severe. In this pilot study, we attempted an objective evaluation of CIPN using a quantitative pain measurement system (Pain Vision®). Methods The subjects were patients with gynecologic cancer who underwent chemotherapy using taxane and platinum drugs. The grade of the peripheral sensory nerve disorder was based on the Common Terminology Criteria for Adverse Events (CTC-AE) ver. 4.0 and was evaluated before the initiation of therapy and up to six chemotherapy cycles. A symptom scale assessed by the patients using a peripheral neuropathy questionnaire (PNQ) was also evaluated. Simultaneously during these evaluations, graded electric current was applied from the probe to a fingertip and measured both the lowest perceptible current and lowest current perceived as pain by Pain Vision®. From these values, the pain degree was calculated from the following formula: (pain perception current value - lowest perceptible current value) ÷ lowest perceptible current value × 100. We compared the pain degrees by Pain Vision® during CIPN development with the value obtained before chemotherapy initiation. Results Forty-one patients were enrolled. In the evaluation by a medical professional, 28 (64.3%) patients developed CIPN during 2.5 ± 1.1 chemotherapy cycles (mean ± standard deviation). The pain degree by Pain Vision® at grade 1 and 2 CIPN development according to the evaluation (CTC-AE) was significantly decreased compared to that before chemotherapy initiation (126.0 ± 114.5 vs. 69.8 ± 46.8, p = 0.001, and 126.0 ± 114.5 vs. 32.8 ± 32.6, p = 0.004). Changes in the pain degree by Pain Vision® were also found during scale B and C, D CIPN development in the patient evaluation (PNQ) (115.9 ± 112.4 vs. 70.6 ± 56.5, p = 0.005, and 115.9 ± 112.4 vs. 46.3 ± 42.9, p = 0.004). In the 13 patients in whom CIPN did not occur, no significant decrease in the pain degree by Pain Vision® was detected (p = 0.764). There was no discontinuation of the measurements because of adverse events such as discomfort from the electric current. Conclusion The decrease in the pain degree measured by Pain Vision® was associated with the onset of CIPN symptoms. Particularly, detection of CIPN by Pain Vision® was possible, though most of the CIPN that occurred was low grade or mild symptom. Pain Vision® might become a noninvasive and convenient objective CIPN detection tool to supplement subjective CIPN evaluation. Trial registration The study approval number in the institution; H25-140. Registered December 17, 2013.